Underemployment in South Africa. Issue 1 (2nd January 2017) - Beukes, Rochelle; Fransman, Tina; Murozvi, Simba; Yu, Derek
ABSTRACT: With the introduction of the Quarterly Labour Force Survey since 2008, a newly derived variable, namely underemployed, has become available. It is derived according to the 'time-related' approach (i.e. those who are employed, but would like to work longer hours and are available to work longer hours in the near future). However, underemployment could also be derived according to the 'inadequate employment situations' approach (e.g. under-utilisation of skills, over-qualification). Because underemployment is a seriously under-researched topic in South Africa, this article investigates the extent of underemployment according to these two definitions, before examining whether the characteristics of the two groups of underemployed are significantly different.